ENGLISH AS A LINGUA FRANCA: INCORPORATING ELF TO EFL CLASSROOM - Mutiaraningrum, Ira (UHN IGB Sugriwa Denpasar, 2025)
A plethora of studies envisaging English as a lingua franca has been provided in the literature. Studies examining the relationship between English as a lingua franca and English as a foreign language has been emerged sparking excitement among language practitioners. This conceptual paper endeavors to approach English as a lingua franca and English as a foreign language. Employing traditional literature review, this study provides an overview, structures argument, and provides context for new research using thematic discussion. This narrative literature review taps further into the application of English as a lingua franca in English as a foreign language classroom. A thought-provoking issue regarding the position of English as a lingua franca versus English as a foreign language has ignited considerable debate among scholars. Reflecting upon studies presented in this paper, it is summarized that the existence of English as a lingua franca does not replace English as a foreign language. This study also describes the activities that language instructors might consider in integrating English as a lingua franca in English as a foreign language classroom. This study offers unique contribution by offering pedagogical innovation that bridges the concept of English as a Lingua Franca (ELF) and English as a Foreign Language (EFL).